Presión tributaria y la recaudación fiscal: El caso de la curva de Laffer en el Perú, 1990-2021 - Alvarado López, Kathia Elizabeth (2022)
The main objective of this investigation is to determine the incidence between tax pressure and tax collection for the Peruvian case during the period 1993-2019. This study is of a non-experimental type of longitudinal and correlational cutting. It was found that the tax pressure has a direct and significant incidence. In addition, the rate that maximizes tax collection, using the proposed econometric model is: 26.37%. Tax revenues reflect an annual growth rate of 10.2% while the tax pressure shows an annual growth rate of 1.80%. With respect to the model applied to find the Laffer curve, the variations of the variables included explain 89.4% of the variations in tax collection in Peru, from 1990 to 2021.